The dilemma of ischemic heart failure; how FDG-PET can guide therapy and improve outcomes? Case report - Mohamed A. Mandour Ali; Sallam Lotfy; Ibrahem M. Koura; Mahmoud Derbala; Adel H. Allam (The Egyptian Heart Journal, 2013)
Patients with ischemic LV dysfunction are at increasing risk of adverse cardiac events including sudden cardiac death. Proper revascularization of viable ischemic myocardium (compared to medical treatment alone) is associated with improvement of LV systolic function, less cardiac morbidities & mortalities and better functional capacity and well-being. Many diagnostic tools are used in clinical practice for assessment of myocardial viability. Dobutamine stress Echocardiography (DSE) is the most widely used technique, while delayed enhancement cardiac magnetic resonance (DE-CMR) and Flourine-18-fluorodeoxy-glucose positron emission tomography (18F-FDG PET) are considered the standard of care for assessment of myocardial viability. Our case report illustrates how FDG PET myocardial viability assessment can guide therapy and improve outcomes in a difficult clinical and angiographic situation.